LOCAL COMMUNITY EMPOWERMENT IN ENHANCING THE QUALITY OF HOMESTAY AND CULINARY MANAGEMENT IN KAMPUNG ADAT BALAI KALIKI PAYAKUMBUH CITY - Hendri Azwar; Anni Faridah; Elida Elida; Feri Ferdian; Retnaningtyas Susanti (Community Development Journal : Jurnal Pengabdian Masyarakat, 2026)
This community empowerment program focuses on enhancing the quality of homestay and local culinary management in the Balai Kaliki Adat Village, Payakumbuh City, West Sumatra. Despite its rich cultural heritage and tourism potential, the village faces challenges in the standardization of homestay facilities, culinary innovation, and community awareness of cultural hospitality standards. The program implemented participatory training, technical assistance, and collaborative approaches with academic and government partners to advance sustainable community-based tourism. Key outcomes include improved homestay management skills, innovative local culinary products, and strengthened multi-stakeholder cooperation, contributing to cultural preservation and economic growth. This study offers a replicable model for integrating cultural values and community participation in rural tourism development.